Child Protection Peer Review for Paediatricians. (9th April 2012) - Thomas, Amanda; Mott, Alison
<x xml:space="preserve">Abstract</x> Key Practitioner Messages Peer review involves a group of peers engaged in a discussion and providing an opinion on an individual's case that the individual can accept or reject while retaining ultimate responsibility for providing their opinion. Each health organisation employing paediatricians working in child protection should establish peer review processes in line with the recommendations and standards contained within this document and RCPCH Peer Review in Safeguarding (May 2012).